2014
DOI: 10.1159/000369777
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Small Vessel Disease and Renal Function: Systematic Review and Meta-Analysis

Abstract: Background: The small vessel disease (SVD) that appears in the brain may be part of a multisystem disorder affecting other vascular beds such as the kidney and retina. Because renal failure is associated with both stroke and white matter hyperintensities we hypothesised that small vessel (lacunar) stroke would be more strongly associated with renal failure than cortical stroke. Therefore, we performed a systematic review and meta-analysis to establish first if lacunar stroke was associated with the renal funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
71
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 52 publications
3
71
1
Order By: Relevance
“…lacunes, WMH and cerebral microbleeds) and kidney function has been extensively studied before [3][4][5][6][7][8][9]20] . We found that associations with microalbuminuria were present for lacunes, WMH and basal ganglia EPVS (the most frequent marker in our study).…”
Section: Discussionmentioning
confidence: 99%
“…lacunes, WMH and cerebral microbleeds) and kidney function has been extensively studied before [3][4][5][6][7][8][9]20] . We found that associations with microalbuminuria were present for lacunes, WMH and basal ganglia EPVS (the most frequent marker in our study).…”
Section: Discussionmentioning
confidence: 99%
“…Makin and colleagues (2015) tried to study the relation of small vessel (lacunar) stroke with renal impairment with the hypothesis that lacunar infarction would be associated with more renal impairment compared to cortical stroke; however, there was no such difference 20 . We are not able to comment on this as we have not categorized ischemic stroke into these subgroups in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This association appears to be mediated by cognitive impairment onset and might be at least partly explained by the onset of microvascular cerebral lesions, such as white matter lesions, without acute cerebrovascular events [39]. Of notice, the extent of brain microvascular changes has been associated with extra-cerebral end-organ damages in AH, including chronic kidney damage [40], increased left ventricular mass [41], and retinal microvascular changes [42].…”
Section: The Role Of Cognitive and Functional Statusmentioning
confidence: 99%